(untitled) (Journal of Natural Language and Linguistics, 2024)
The study is about how Empowerment, a crucial concept for all teachers, is influenced by the Model of Role Identity and Behavioral Creativity Style among Assistant Language Teachers in Japan. A causal and correlational quantitative approach was used to generalize and to find the relationship between the variables. The data from 268 respondents were collected using Google Form and were analyzed using linear regression analysis. The results revealed that though both have significant relationships with Empowerment, the Model of Role Identity has a greater influence on Empowerment than the Behavioral Creativity Style. This showed the importance of Kanter’s theory of structural empowerment, in this case where ALTs with a much clearer role and who were not in isolation within the structure were more empowered. This implies that one factor in increasing the empowerment, and thereby the effectiveness, of ALTs, is the need for greater Model of Role Identity.